Utilization of a novel patient-specific 3D-printing template for percutaneous endoscopic transforaminal discectomy: results from a randomized controlled trial - Huang, Xin; Luo, Qipeng; Liang, Chen; Wang, Yixuan; Jia, Donglin; Li, Shuiqing; Guo, Xiangyang (Frontiers in Neuroscience, 2024)
Background: The learning curve for percutaneous endoscopic transforaminal discectomy (PETD) is steep, especially for the puncturing and localization procedures. The implementation of 3D printing technology may solve this problem. Methods: A novel individualized 3D-printing template (3D-PT) was designed and utilized in PETD. A prospective randomized controlled trial was performed. A total of 28 patients with lumbar disc herniation treated with PETD were analyzed. Of these, 14 patients were treated with the assistance of 3D printing technology (3D-PT group) in conjunction with fluoroscopy, while the remaining 14 patients were treated exclusively under the guidance of C-arm fluoroscopy (control group). Results: The number of puncture attempts in the 3D-PT group was significantly less than in the control group (1.36 ± 0.63 vs. 6.07 ± 3.08, p=0.000). The 3D-PT group exhibited a significant reduction in both intraoperative puncture fluoroscopies (2.71 ± 1.27 vs. 12.14 ± 6.15, p=0.000) and the overall number of fluoroscopies (2.71 ± 1.27 vs. 17.43 ± 6.27, p=0.000). In the 3D-PT group, there was a significant reduction in both the puncture time (5.77 ± 1.82 vs. 13.99 ± 4.36, p=0.000) and the total operation time (60.39 ± 9.78 vs. 76.25 ± 17.78, p=0.007). Complications were not observed in either group. Conclusion: The application of the novel individualized 3D-PT for PETD is effective and safe. The technique has substantial potential and is worth widely promoting.